Developing Students’ Higher Order Thinking Skills (HOTS) in Reading: English Teachers’ Strategies in Selected Junior High Schools - Indriyana, Bernadeta Siska; Kuswandono, Paulus (JET (Journal of English Teaching), 2019)
The 2013 curriculum in Indonesia mandates that teachers should develop students’ Higher Order Thinking Skills (HOTS). One of the learning goals through HOTS is to make sure that students can analyze, evaluate, and create their knowledge. However, studies on HOTS issues in English learning, particularly in reading skills, are still very limited. Therefore, this study aimed at describing the teachers’ strategies in developing HOTS in teaching reading skills. The researcher used a mixed-method, as it is relevant to the methodology needed in this study. The participants were 22 English teachers of Junior High Schools in Yogyakarta. The data were collected through questionnaires, observations, and interviews. The findings indicated that the strategies by the teachers to develop HOTS were as follows: (1) asking divergent questions to the students, (2) using group discussions, (3) informing learning objectives to the students, (3) giving feedback to invite the students to review, refine, and improve understanding about learning materials, and (5) giving motivation to the students to think critically. The recommendation for further study is also discussed.